2009
DOI: 10.1111/j.1365-2958.2009.06783.x
|View full text |Cite
|
Sign up to set email alerts
|

PPE and PE_PGRS proteins of Mycobacterium marinum are transported via the type VII secretion system ESX‐5

Abstract: SummaryESX-5 is one of the five type VII secretion systems found in mycobacteria. These secretion systems are also known as ESAT-6-like secretion systems. Here, we have determined the secretome of ESX-5 by a proteomic approach in two different strains of Mycobacterium marinum. Comparison of the secretion profile of wild-type strains and their ESX-5 mutants showed that a number of PE_PGRS and PPE-MPTR proteins are dependent on ESX-5 for transport. The PE and PPE protein families are unique to mycobacteria, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
320
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 242 publications
(345 citation statements)
references
References 57 publications
23
320
0
Order By: Relevance
“…Immunoblot analysis showed that both PE25-HA and PPE41 were secreted in the WT strain, but hardly in the ESX-5 mutant (Fig. 1A), similar to what has been described for PPE41 (20,21). This secretion defect was not accompanied by an increase in cellular levels of PE25 and PPE41.…”
Section: Resultsmentioning
confidence: 49%
See 4 more Smart Citations
“…Immunoblot analysis showed that both PE25-HA and PPE41 were secreted in the WT strain, but hardly in the ESX-5 mutant (Fig. 1A), similar to what has been described for PPE41 (20,21). This secretion defect was not accompanied by an increase in cellular levels of PE25 and PPE41.…”
Section: Resultsmentioning
confidence: 49%
“…Consistently, deletion of ESX-1 genes from the genomes of M. tuberculosis or M. bovis results in diminished virulence (18,19). Of the other ESX loci, both ESX-3, which is involved in iron acquisition, and ESX-5 have been demonstrated to encode functional secretion systems (20)(21)(22).…”
mentioning
confidence: 67%
See 3 more Smart Citations